A progressive model to simulate the full mechanical behavior of concrete segmental lining longitudinal joints. (15th June 2015) - Li, Xiaojun; Yan, Zhiguo; Wang, Zhen; Zhu, Hehua
Highlights: A progressive model is proposed to simulate the full mechanical behavior of the joint. Full-scale tests on full mechanical behavior of the joint are first conducted. The mechanical behavior of the joint can be divided into four loading stages. The prediction of the proposed model can meet well with the experimental data. Bolt location and axial load has great influence on the joint mechanical behavior. Abstract: The longitudinal joint is the most critical component for determining the mechanical response of concrete segmental linings. Existing longitudinal joint models are mainly developed for the analysis of segmental lining design, but the real behavior of longitudinal joint may exceed the normal design range during the operation. In this study, full-scale tests on the longitudinal joint which is adopted by the Shanghai Metro Line No. 13 are first conducted. The longitudinal joint is continuously loaded until it is completely damaged. The tests reveal that the mechanical behavior of the longitudinal joint can be divided into four loading stages in both the sagging moment and hogging moment cases. Based on the test observations, a progressive model is proposed to simulate the full mechanical behavior of the joint. The model consists of a series of stress states. Each stress state corresponds to a load bearing mode of the joint which is observed in the tests. The contributions of the concrete, bolt, and gasket to the mechanical behavior of the joint are included in the model. The structure details such as the gaps between the two concrete segments on the internal and external edges of the joint are also considered. The proposed model is verified by the test results. Finally, the influences of the bolt pretightening force, bolt location, axial load, and gasket on the mechanical behavior of the joint are investigated using the proposed model.